1974
DOI: 10.1104/pp.54.6.877
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Physiological Changes in Sugar Beet Leaves during Sink to Source Conversion

Abstract: The onset of export during leaf development was correlated with changes in metabolism and ultrastructure and with patterns of solute distribution in the developing seventh leaf of sugar beet (Beta vulgaris L.) in order to study the cause of initiation of translocation. Infrared gas analysis of carbon dioxide uptake showed a broad peak for net photosynthesis dm(2 at 35 to 40% final laminar length. Pulse labeling with 14CO2 demonstrated that maximum import of translocate occurred at 25% final laminar length; exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
77
0
1

Year Published

1977
1977
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 35 publications
7
77
0
1
Order By: Relevance
“…This change is paralleled by the development of sucrose phosphate synthase activity rather than by a decrease of the sucrose-hydrolyzing enzymes (12). In the same material, phloem loading begins 35 to 45 h prior to onset of export, and it has been suggested that this triggers the initiation of export by increasing sufficiently the solute concentration within the conducting cells (7).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This change is paralleled by the development of sucrose phosphate synthase activity rather than by a decrease of the sucrose-hydrolyzing enzymes (12). In the same material, phloem loading begins 35 to 45 h prior to onset of export, and it has been suggested that this triggers the initiation of export by increasing sufficiently the solute concentration within the conducting cells (7).…”
mentioning
confidence: 87%
“…Apart from its central role in leaf development, this transition provides a straightforward system to compare sink and source tissue without dealing with the complications introduced by the study of different organs (27). The sink/source transition of the leaf is a highly integrated process beginning when the leaf has reached about 35% final lamina length, and proceeds from the tip to the base (7). The transition is made possible by a series of changes affecting both metabolism and transport.…”
mentioning
confidence: 99%
“…Discs were also obtained from young sink leaves (3-4 cm in length) in which the lower portion of the leaf lamina was still unrolled. Previous studies (9,17) …”
Section: Introductionmentioning
confidence: 99%
“…For most plants, this occurs by loading Suc into the phloem and transporting it from source tissues (net exporters) to sink tissues (net importers), where Suc is unloaded (Turgeon, 1989;van Bel, 2003). This process is well characterized at the physiological, biochemical, and anatomical levels (Hofstra and Nelson, 1969;Fellows and Geiger, 1974;Evert et al, 1978;Nguyen-Quoc et al, 1990;Huber and Hanson, 1992;Evert et al, 1996a;Koch, 1996;Paul and Foyer, 2001). However, despite the obvious importance of this process for plant growth and development, few genes that function in carbon partitioning have been identified.…”
mentioning
confidence: 99%